Kinetics of grain material drying in installations with intermittent energy supply by microwave and infrared radiation - Kalinichenko, Roman; Bandura, Valentyna; Kotov, Borys; Pantsyr, Yurii; Garasymchuk, Ihor; Stepanenko, Serhii (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2026)
In both microwave and infrared grain treatment methods, selective heating of the moist material occurs since moisture (water) components selectively absorb energy with greater intensity, ensuring targeted energy delivery, as only the water content heats up rather than the structural matrix of the material. Since moisture is evenly distributed throughout the material volume, heating occurs uniformly throughout the body. Based on the analysis of typical generalized equations of coupled heat and mass transfer, mathematical models of the grain material drying process in the microwave electromagnetic field and infrared radiation were formulated. Using experimental data on grain drying, parametric identification of the developed mathematical models for the drying process dynamics under intermittent MW and IR energy supply was performed. An algorithm for calculating unsteady drying regimes was developed. The MW-IR dryer ensures environmentally friendly grain drying with increased energy efficiency. The influence of operating parameters on the drying kinetics in a dryer with MW and IR energy supply was determined. Rational parameters of microwave-IR treatment: microwave power – 600 W/dm3, IR: 940 W/m2 – for the first period; 1130 W/m2 – for the second period; 1210 W/m2 – for the third period. Experimental studies confirmed the high efficiency of electromagnetic energy supply to the drying material – the intensity of moisture removal was more than twice as high compared to convective drying. It is established that the use of a combined energy supply in the process of grain material drying reduces specific energy consumption and intensifies moisture removal without overheating the material.